1987
DOI: 10.1038/bjc.1987.113
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis by flow cytometry, response to endocrine treatment and prognosis in advanced carcinoma of the breast

Abstract: Summary The relationship between DNA content of mammary cancer and subsequent response to endocrine therapy was studied in 136 patients with advanced disease. All were treated with tamoxifen or ovarian ablation as first-line systemic therapy after relapse and were evaluable for response according to UICC criteria. DNA characterisation by flow cytometry was used on formalin fixed paraffin-embedded samples of tumour. Tumours were grouped according to DNA index into diploid (n = 52, 38%), 'tetraploid' (n =46, 34%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 26 publications
(38 reference statements)
3
30
1
Order By: Relevance
“…The technique has gained some popularity, since flow cytometric histograms are rapid to produce and often easy to interpret. It has been suggested that breast carcinomas with an abnormal (non-diploid or aneuploid) nuclear DNA content are associated with less favourable prognosis than carcinomas with a normal (diploid) DNA content (Hedley et al, 1984(Hedley et al, , 1987Coulson et al, 1984;Ewers et al, 1984;Thorud et al, 1986;Baildam et al, 1987;Cornelisse et al, 1987;Kallioniemi et al, 1987;Stal et al, 1989). Similarly, the DNA index (DI, the relative DNA content of an aneuploid stemline of cells as compared with diploid cells) and the percentage of S-phase cells in the DNA histogram (S-phase fraction, SPF) have been found by some to be of prognostic significance (Dowle et al, 1987;Hedley et al, 1987;Kallioniemi et al, 1988;Stal et al, 1989;McDivitt et al, 1986;Klintenberg et al, 1986).…”
mentioning
confidence: 99%
“…The technique has gained some popularity, since flow cytometric histograms are rapid to produce and often easy to interpret. It has been suggested that breast carcinomas with an abnormal (non-diploid or aneuploid) nuclear DNA content are associated with less favourable prognosis than carcinomas with a normal (diploid) DNA content (Hedley et al, 1984(Hedley et al, , 1987Coulson et al, 1984;Ewers et al, 1984;Thorud et al, 1986;Baildam et al, 1987;Cornelisse et al, 1987;Kallioniemi et al, 1987;Stal et al, 1989). Similarly, the DNA index (DI, the relative DNA content of an aneuploid stemline of cells as compared with diploid cells) and the percentage of S-phase cells in the DNA histogram (S-phase fraction, SPF) have been found by some to be of prognostic significance (Dowle et al, 1987;Hedley et al, 1987;Kallioniemi et al, 1988;Stal et al, 1989;McDivitt et al, 1986;Klintenberg et al, 1986).…”
mentioning
confidence: 99%
“…Following the paper of Hedley et al (1983) describing flow cytometric analysis of DNA using formalin-fixed and paraffin-embedded tissues, numerous studies have been published confirming the application of their method to archival material (Friedlander et al, 1984;Hiddemann et al, 1984;Coon et al, 1986;Douglas et al, 1986;Schmidt et al, 1986;Baildam et al, 1987). Until then, information on the DNA content of tumours was obtained using either Feulgen microspectrophotometry, which is a painfully slow procedure allowing only a small number of cells to be examined, or flow cytometry, which needed fresh unfixed tissue or karyotyping (Atkin, 1972;Mann & Yates, 1979).…”
mentioning
confidence: 99%
“…There is good evidence from both static and flow cytometric DNA analysis of paraffin embedded material or freshly excised tissue that patients with DNA diploid tumours are likely to have a better prognosis than their DNA aneuploid counterparts (Auer et al, 1980;Baildam et al, 1987;Kallioniemi et al, 1987a, b). We have recently reported that sufficient cellular material for meaningful flow cytometric DNA analysis can be obtained from the majority of routine diagnostic FNAs (Levack et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…While there was no variation between sequential FNAs in four patients, marked differences in the DNA profile were observed in the remaining nine patients undergoing treatment, the changes not necessarily being associated with clinical response to therapy. It is concluded that the monitoring of cellular changes by DNA analysis of sequential FNAs may be complex and subject to problems associated with heterogeneity.Flow cytometric DNA analysis can provide useful information on the cellular characteristics of breast tumours (Auer et al, 1980;Baildam et al, 1987;Cornelisse et al, 1987;Dowle et al, 1987; Kallioniemi et al, 1987a, b;Owainati et al, 1987). Recently, we demonstrated that fine needle aspiration of most breast cancers can provide sufficient cellular material for meaningful analysis of DNA profiles using flow cytometry (Levack et al, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation